Explaining export diversification: an empirical analysis - Bebczuk, Ricardo Néstor (2006)
Although many papers have dealt with the relation between trade structure and economic growth, much less attention has been paid to the underlying determinants of export diversification, an exercise that should provide valuable research and policy recommendations regarding the room for active government interventions and their expected outcomes. To fill this gap, this project aims to investigate this issue by: (1) employing econometric techniques on a cross-country database; (2) analyzing, as a case study, firm-level export diversification in Argentina. As a result of the pronounced real devaluation of the peso in 2002-2004, this country offers a nice quasi-natural experiment to examine whether relative prices might influence export diversification and to observe whether diversification is a between- or within-firm phenomenon.